REVIEW OF SECURITY CHALLENGES WITH IOT FOR INDUSTRY SUCH AS SCADA SYSTEM - Kumar, Surjeet; Yadav, Prashant Kumar (International Journal of Engineering Technology and Computer Research, 2018)
Information has brought an important transformation in organizations with high impacts, which are comparable to the mechanization and electricity brought in the first and second industrial revolution. This evolvement has promoted the emergence of cloud-based systems, the Internet of Things (IoT), Big Data, Industry 4.0, BYOD (Bring Your Own Device) and CYOD (Choose Your Own Under the concept of "Industry 4.0", production processes will be pushed to be increasingly interconnected, information based on a real time basis and, necessarily, much more efficient. In this context, capacity optimization goes beyond the traditional aim of capacity maximization, contributing also for organization’s profitability and value. Indeed, lean management and continuous improvement approaches suggest capacity optimization instead of maximization. Now-a-days, a new generation of computing technology i.e. Internet of Things (IoT) is taking place. IOT is a Network of intelligent things, connected together using the concept of cloud to make our lives much easier and safer and to reduce our impact on the environment. Every organization such as companies and civil institutions needs up-to-date information about people. In this regard, most establishments either use websites, emails or notice boards. However, in most of countries internet access is available to people on systems and their mobile devices, so that the transferring of the information can be much easier and less costly through the internet. IoT uses internet to establish connection between things and user, hence security concern of that communication channel will become important. Here we will discuss about security issues, arise in IoT communication. Keywords: Arduino, RaspaberryPi, Cryptography, PKI.